NILAI-NILAI ISLAM PADA BUDAYA TAKZIYAH MASYARAKAT GADING CEMPAKA KOTA BENGKULU - Yunita, Nurma; Ruhan, Siun; Azizi, Arief; Agusten, Agusten; Sejati, Sugeng; Japarudin, Japarudin; Mahdi, Imam (IAIN Pontianak, 2023)
Implementing local traditions and culture in their religious behavior, many do not have Islamic values, some even conflict with Islamic teachings. However, basically culture is something that is quite central in human life. Culture and traditions are also inherent in a particular community group and a particular religion. In the city of Bengkulu there is a Takziyah tradition, which has its own uniqueness and method of implementation. This research aims to describe and explain again how Islamic values are in local traditions and culture of worship in Bengkulu City, in terms of Islamic Law. This research is field research, which examines phenomena directly, as well as reviewing literature related to takziyah. This research concludes that Takziyah in Bengkulu City has Islamic values, namely: the value of helping, the value of solidarity, the value of faith, the value of tolerance and the value of responsibility.